Perception and adaptation of the producers to the impacts of climate change in apple production: an assessment of Mustang District of Nepal - Khanal, Uttam (Journal of Agriculture and Environment, 2014)
A study was conducted to assess the perception of farmers, researchers and related stakeholders on the impacts of climate change in apple production in Mustang district of Nepal. Focus group discussion (FGD) and key informants interviews were organized to explore the major climate hazards, relationship of climate hazards to apple production, impacts of climate change and potential adaptation measures. Increased temperature, drying up of water resources, increased northern wind, high speed wind, less snowfall and prolonged droughts were found as the major climatic hazards in the district. Use of alternative and/or additional sources of irrigation water; use of low chilling, drought tolerant and early maturing varieties; adoption of efficient irrigation methods and conservation agriculture practices were identified as the important adaptation measures.